Globalization and its Contribution to Islamic Education Innovation in Indonesia - Andika Apriansyah; Karoma; Fajri ismail (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The impact of globalization on Islamic education is examined in this essay. Literature is a source of data collected. Literature in the form of books, journals and online sources was used to collect data. Content analysis is a research process used for analysis, because it is based on documents. The conclusion of the discussion shows that, in facing globalization, Islamic education has new opportunities and obstacles. Therefore, initiatives are needed such as improving the quality of teachers, updating learning materials, awareness of the importance of technology, internalization of religious principles, and collaboration with the community. These efforts need to be made so that Islamic education continues to follow developments with the times. Islamic education seeks to combat globalization by offering quality educational resources, helping students internalize religious values, updating its materials, combining religious and general knowledge, collaborating with the community, and managing its operations through information technology.